2017
DOI: 10.1021/acsomega.7b00669
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Design of CuS Architectures for Visible Light Photocatalysis of 4-Chlorophenol

Abstract: Hydrothermal-assisted CuS hierarchical architectures were grown in the presence of anionic sulfur sources, and the investigation of their degradation efficiency for a pesticide 4-chlorophenol (4-CP) under visible light irradiation was carried out. The dissociation of S 2– from the sulfur compound governs the nucleation of CuS followed by a specific pattern of growth to produce different morphologies. The self-assembled covellite spherical CuS flower architecture assembles in the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
66
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(84 citation statements)
references
References 54 publications
(104 reference statements)
18
66
0
Order By: Relevance
“…A number of studies have reported on the value and nature of the energy band gaps of covellite CuS thin films. The direct band gaps reported in the literature lie in the range from 2.05 to 2.58 eV [3,12,16,20]. The band gaps of CuS thin films prepared in this study also ranged from 2.47 to 2.68 eV.…”
Section: Photovoltaic Performance Of Cus/sns Absorber-based Solar Cellsmentioning
confidence: 51%
See 2 more Smart Citations
“…A number of studies have reported on the value and nature of the energy band gaps of covellite CuS thin films. The direct band gaps reported in the literature lie in the range from 2.05 to 2.58 eV [3,12,16,20]. The band gaps of CuS thin films prepared in this study also ranged from 2.47 to 2.68 eV.…”
Section: Photovoltaic Performance Of Cus/sns Absorber-based Solar Cellsmentioning
confidence: 51%
“…Atomic vibration mode analysis can distinguish spatial variations and surface species in a sample composition, which is generally possible through Raman measurement [16]. Additional analysis of the structural properties of the CuS thin films was conducted by obtaining Raman spectra, and the results are shown in Figure 2.…”
Section: Cus Thin-film Structural Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19][20] Recently, copper suldes have attracted a great deal of attention owing to their widespread applications in solar cells, optical lters, photoelectric transformers, superconductors and sensors. [21][22][23] Particularly, covellite (CuS) has a strong p-type metallic character with the highest concentration of free carriers among copper sulde materials. 24 Many previous researchers have demonstrated that CuS has important applications for photocatalysis.…”
mentioning
confidence: 99%
“…21 The morphological evolutions of the Cu 2 S and Cu 2 MoS 4 products were investigated by reacting the octahedral Cu 2 O template with sodium molybdate and thioacetamide in ethylene glycol. [25][26][27][28] The S 2− ions in solution reacted at the surfaces of the octahedral Cu 2 O template to form thermodynamically stable Cu 2 S nanoparticles on these surfaces. The mole ratio of thioacetamide to sodium molybdate was fixed at 5.48.…”
Section: Resultsmentioning
confidence: 99%